Vacancies in GaN bulk and nanowires: effect of self-interaction corrections - Carter, Damien; Fuchs, M.; Stampfl, C. (Institute of Physics Publishing Ltd., 2012)
We investigate gallium and nitrogen vacancies in gallium nitride (GaN) bulk and nanowires using self-interaction corrected pseudopotentials (SIC). In particular, we examine the band structures to compare and contrast differences between the SIC results and standard density functional theory (DFT) results using a generalized gradient approximation (GGA) (Perdew et al 1996 Phys. Rev. Lett. 77 3865) functional. For pure nanowires, we observed similar trends in the bandgap behaviour, with the gap decreasing for increasing nanowire diameters (with larger bandgaps using SIC pseudopotentials). For gallium vacancies in bulk GaN and GaN nanowires, SIC results are similar to DFT-GGA results, albeit with larger bandgaps. Nitrogen vacancies in bulk GaN show similar defect-induced states near the conduction band, whilst a lower lying defect state is observed below the valence band for the DFT-GGA calculations and above the valence band for the SIC results. For nitrogen vacancies in GaN nanowires, similar defect states are observed near the conduction band, however, while the SIC calculations also show a defect state/s above the valence band, we were unable to locate this state for the DFT-GGA calculations (possibly because it is hybridized with edge states and buried below the valence band).